ALL-SKY CAMERAS FOR OBSERVATION AND INVESTIGATION OF VARIABLE STARS AND METEOR SHOWERS - Bryukhanov, I. S.; Sergey, I. M.; Vatutina, V.; Ivchik, A.; Pogodina, M.; Vatolin, R.; Dovnar, S.; Osadchaya, V.; Tabolich, A.; Tabolich, V.; Lyudimov, A.; Smolenchuk, T.; et al. (Одеські астрономічні публікації, 2013)
This paper studies the capabilities of the all-sky weather (meteorological) cameras in investigation of bright variable stars and determination of apparent radiants of meteor showers.